Effects of the neurological wake-up test on clinical examination, intracranial pressure, brain metabolism and brain tissue oxygenation in severely brain-injured patients - Helbok, Raimund (BioMed Central, 2012)
INTRODUCTION: Daily interruption of sedation (IS) has been implemented in 30 to 40% of intensive care units worldwide and may improve outcome in medical intensive care patients. Little is known about the benefit of IS in acutely brain-injured patients. METHODS: This prospective observational study was performed in a neuroscience intensive care unit in a tertiary-care academic center. Twenty consecutive severely brain-injured patients with multimodal neuromonitoring were analyzed for levels of brain lactate, pyruvate and glucose, intracranial pressure (ICP), cerebral perfusion pressure (CPP) and brain tissue oxygen tension (P(bt)O(2)) during IS trials. RESULTS: Of the 82 trial days, 54 IS-trials were performed as interruption of sedation and analgesics were not considered safe on 28 days (34%). An increase in the FOUR Score (Full Outline of UnResponsiveness score) was observed in 50% of IS-trials by a median of three (two to four) points. Detection of a new neurologic deficit occurred in one trial (2%), and in one-third of IS-trials the trial had to be stopped due to an ICP-crisis (> 20 mmHg), agitation or systemic desaturation. In IS-trials that had to be aborted, a significant increase in ICP and decrease in P(bt)O(2 )(P < 0.05), including 67% with critical values of P(bt)O(2 )< 20 mmHg, a tendency to brain metabolic distress (P < 0.07) was observed. CONCLUSIONS: Interruption of sedation revealed new relevant clinical information in only one trial and a large number of trials could not be performed or had to be stopped due to safety issues. Weighing pros and cons of IS-trials in patients with acute brain injury seems important as related side effects may overcome the clinical benefit.